Accessibility to Riga Public Transport Services for Transit Passengers. (2017) - (Jackiva), Irina Yatskiv; (Budiloviča), Evelina Budilovich; Gromule, Vaira
Abstract: The research suggests the concept of more public transport-oriented cities that accessible for transit passengers and considers the role of Riga public transport system in determining the level of accessibility for different spatial aspects, which in turn facilitates the creation of economies of scale, agglomeration effects and networking advantages. Authors consider long distance travels and assess accessibility and connections between the Riga city and the key destinations in the Latvian regions and Baltic states. It involves the entire urban transport system, regional and international network and, also, long distance terminal in chain of movements.